MODEL OF PRICING STRATEGY, INSTAGRAM SOCIAL MEDIA & SERVICE QUALITY TO THE PURCHASE DECISION MAKING (CASE STUDY OF SEVEN FASHION SHOPS) - Vincent Didiek Wiet Aryanto; Wisit Rittiboonchai; Amjad Ali; Imang Dapit Pamungkas; Yulita Setiawanta (Fakultas Ekonomi dan Bisnis Universitas Dian Nuswantoro, 2023)
The purpose of this study is how does the influence of price affect purchasing decisions at fashion stores, Instagram social media influence purchasing decisions at fashion stores and influence of service quality considerably influence the purchase decision at a fashion store. This study used 100 respondents who were taken from consumers who had shopped at 7 Fashion Stores and the data was processed using SmartPLS. Based on the results of the research that has been done, prices have a positive and significant effect on purchasing decisions. Instagram social media has no positive and insignificant effect on purchasing decisions. Consumers are more interested in shopping in person than on social media Instagram. Service quality has a positive and significant effect on purchasing decisions. This means that the quality of service provided by fashion stores makes consumers feel comfortable when shopping. Furthermore, providing good service quality will make consumers become repeat customers.